Surgical management of adult choledochal cysts - Thawatchai Akaraviputh (2018)
Objectives: Results of the surgical management of 17 choledochal cysts in adults at the Department of Surgery, Siriraj Hospital, Mahidol University, are presented. Material and Method: All the patients who underwent diagnosis and were surgically managed during the period between October 1990 and January 1999 were analyzed retrospectively. Cysts were classified anatomically according to the descriptions of Todani et al. The authors assessed the clinical features, operative procedure and outcome of the patients. Results: There were 15 females and 2 males, with ages ranging from 16-45 years. Only 2 patients (11.8%) had the clinical triad: jaundice, abdominal pain and mass. Clinical pancreatitis was presented in 3 patients (17.6%). There were 10 type I (58.8%), 6 type IVa (35.3%) and one type V (5.9%) according to Todani's classification. Cholangiocarcinoma was found in one patient (5.9%). Extrahepatic cyst excision with a Roux-en-Y hepatico-jejunostomy was performed on 16 patients with type I or IVa cysts (94.1%). There were no surgical deaths or complications. Ten survivors are well. The authors lost contact with 6 patients during follow-up (35.2%). The median follow up was 3.2 years. The patient with cholangiocarcinoma died 2 years after treatment. Conclusion: This experience recommends total extra-hepatic cyst excision with Roux-en-Y hepaticojejunostomy as the treatment of choice for adult choledochal cyst type I and IV to eliminate the risk of recurrent cholangitis and malignancy.